Moral communities and jailhouse religion: religiosity and prison misconduct - Meade, Benjamin (Criminal justice: recent scholarship, 2014)
Introduction -- Religion, religiosity, and deviance -- Inmate misconduct: theory and evidence -- Religion and corrections -- Studying the relationship between religiosity and inmate misconduct -- The effects of religiosity on inmate misconduct -- Conclusion